Implementation of Self-Directed Learning Policy in The Internship Program (MSIB) at PT Mikro Bisnis Digital Sejahtera - Setyawan, Aji; Fatimah, Nurul (PT ARRUS Intelektual Indonesia, 2024)
This research aims to determine the implementation of Merdeka Belajar policy in the Internship Program (MSIB) at PT Mikro Bisnis Sejahtera. This type of research is qualitative, which was carried out at PT Mikrobisnis Digital Sejahtera. Data sources used primary and secondary data. Primary data employed observations and interview results. Interviews were conducted in a semi-structured manner with four informants in this research, divided into two main informants and two supporting informants. Secondary data utilized company data, books, scientific literature, and the data analysis technique uses qualitative data analysis. The research results indicated that the implementation of the Merdeka curriculum had been carried out in PT Mikrobisnis Digital Sejahtera, which is a company that provides digitalization programs. Combining an approach with the principles of experiential learning and deep student involvement, internship programs can become an effective way to prepare students for success in the world of work. At the end of the learning, there is a capstone project. This is the final project of the program to complete the project directly with the specified one.